Stimulatory Effect of Magnetite Nanoparticles on a Highly Enriched Butyrate-Oxidizing Consortium - Fu, Li; Song, Tianze; Zhang, Wei; Zhang, Jie; Lu, Yahai (Frontiers in Microbiology, 2018)
Syntrophic oxidation of butyrate is catabolized by a few bacteria specialists in the presence of methanogens. In the present study, a highly enriched butyrate-oxidizing consortium was obtained from a wetland sediment in Tibetan Plateau. During continuous transfers of the enrichment, the addition of magnetite nanoparticles (nanoFe3O4) consistently enhanced butyrate oxidation and CH4 production. Molecular analysis revealed that all bacterial sequences from the consortium belonged to Syntrophomonas with the closest relative of S. wolfei and 96% of the archaeal sequences were related to Methanobacteria with the remaining sequences to Methanocella. Addition of graphite and carbon nanotubes (CNTs) for a replacement of nanoFe3O4 caused the similar stimulatory effect. Silica coating of nanoFe3O4 surface, however, completely eliminated the stimulatory effect. The control experiment with axenic cultivation of a Syntrophomonas strain and two methanogen strains showed no effect by nanoFe3O4. Together, the results in the present study support that syntrophic oxidation of butyrate is likely facilitated by direct interspecies electron transfer in the presence of conductive nanomaterials.